The Kerykeion mint control linked coinage of Andragoras and Sophytes - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2020)
Since the preparation of a study published in 2019 on the typology and significance of the eastern imitative Athenian coinage previously attributed to Baktria, and the associated mint control linked issues of Andragoras and Sophytes, a large hoard of these coins progressively entered the numismatic market over three years from late 2017. This has more than doubled the number of examples of the coinage previously known and yielded a number of new mint control types. These extend the typology established in the study and confirm the interpreted relative chronology of the eight series of emissions that comprise the coinage. This essay details two of the newly identified types bearing the kerykeion mint control and their significance within the established typological framework.